آیاتِ مبایعہ کے تناظر میں خواتین کا تربیتی نصاب - Gull, Nayyab; Imran, Dr. Hafiz Muhammad (Al-Irfan, 2022)
Islam has given equal importance the both males and females, in its whole teachings. Besides of this, Quran has especially addressed and discussed the women to build their social characters. Ayat-e-Mubaya’a is called a charter of Islamic training, in which Allah Almighty explained five women’s feature those make them positive in their conduct, as well as described the shirk. The five forbidden things: theft, adultery, murder of children, slander and disobedience of good-deeds are the meangs of a peaceful, containing social values and a joyful married life society. By adopting these qualities, women can give birth to a virtuous society.